Ionic Liquid-Enhanced Assembly of Nanomaterials for Highly Stable Flexible Transparent Electrodes - Yang, Jianmin; Chang, Li; Zhang, Xiqi; Cao, Ziquan; Jiang, Lei (Nano-Micro Letters, 2024)
The controlled assembly of nanomaterials has demonstrated significant potential in advancing technological devices. However, achieving highly efficient and low-loss assembly technique for nanomaterials, enabling the creation of hierarchical structures with distinctive functionalities, remains a formidable challenge. Here, we present a method for nanomaterial assembly enhanced by ionic liquids, which enables the fabrication of highly stable, flexible, and transparent electrodes featuring an organized layered structure. The utilization of hydrophobic and nonvolatile ionic liquids facilitates the production of stable interfaces with water, effectively preventing the sedimentation of 1D/2D nanomaterials assembled at the interface. Furthermore, the interfacially assembled nanomaterial monolayer exhibits an alternate self-climbing behavior, enabling layer-by-layer transfer and the formation of a well-ordered MXene-wrapped silver nanowire network film. The resulting composite film not only demonstrates exceptional photoelectric performance with a sheet resistance of 9.4 Ω sq−1 and 93% transmittance, but also showcases remarkable environmental stability and mechanical flexibility. Particularly noteworthy is its application in transparent electromagnetic interference shielding materials and triboelectric nanogenerator devices. This research introduces an innovative approach to manufacture and tailor functional devices based on ordered nanomaterials. Highlights: 1 We present a method that utilizes ionic liquid-enhanced nanomaterial assembly to fabricate highly stable and large-area MXene-silver nanowire electrodes with ordered layered structures. 2 This approach emphasizes the use of hydrophobic and nonvolatile ionic liquids, which form stable interfaces with water by reducing interface energy, preventing the sedimentation loss of nanomaterials during assembly. 3 The prepared electrodes not only exhibit excellent optoelectronic properties (9.4 Ω sq−1 sheet resistance and 93% transmittance), but also have exceptional antioxidant capacity.